Abdominal fat indicators: anthropometry vs dual energy x-ray absortometry - Marina Kanthack Paccini; Gisela Arsa; Maria Fátima Glaner (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n3p283 Excessive abdominal fat contributes to the development of chronic nontransmissible diseases. Dual emission X Ray absorptiometry (DXA) is a simple to administer technique that allows abdominal fat percentage (%abdominalFDXA) to be determined. Anthropometric measurements, which have been validated and are of low cost, such as the abdominal circumferences 2.5cm above the umbilical scar (ABC2,5) and level with the umbilical scar (ABCum), are used as indicators of abdominal fat. Skin folds (SF) are little used for this purpose. The objective of this study was to verify which of these anthropometric indicators best correlates with and best explains abdominalFDXA. The sample was made up of 22 women (43.9±11.6 years; 34.7±8.3 %G totalDXA) and 18 men (31.9±11.6 years; 19.0±8.0 %G totalDXA) who were measured for ABC2.5, ABCum, suprailiac SF (SI), midaxillary SF (AM) and abdominal SF (AB), while abdominalF (L1-L4) was measured by DXA. Pearson's correlation and multivariate linear regression ("enter" method) were employed to verify the anthropometric measurements' correlations and percentage of explanation with relation to abdominalFDXA. Strong correlations and significant levels of explanation (p<0.05) were observed for both women and men using ABC2.5 (0.90; 81% and 0.89; 78%), ABCum (0.90; 83% and 0.83; 69%), SF AB (0.82; 67%) and SF AM for men (0.81; 66%) and while they were moderate in both sexes for SF SI (0.51; 26% and 0.73; 53%) and for AM in women (0.74; 54%). It was concluded that ABC2.5, ABCum and abdominal skin folds can be used as indicators of abdominal obesity, since they offer the best correlation and greatest explanatory power for abdominal FDXA.